1999
DOI: 10.1243/0954407991526838
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the performance of a split/circulated power transmission

Abstract: A method for the prediction of performance is presented in this paper for the design of a vehicle having a split/circulated power transmission with slip elements and planetary gears. Internal power flow patterns of such systems are also theoretically analysed using mathematical modelling. To estimate the usefulness of the designed power transmission, a geometrical approach is proposed by the performance locus diagram which presents the overall characteristics of the system. This enables complete prediction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Equation (8) shows that the variable factors influencing the basic characteristics of each solution are the structural parameter of the PGT τ and the effective diameter of the TC circuit D. By further analysis, it is found that the efficiency varies strictly monotonically with τ and D. Therefore, the two boundary values for the τ and a specific value for the D are adopted to examine the basic characteristics of each solution. Figure 9 shows the efficiency of each solution.…”
Section: Basic Characteristics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (8) shows that the variable factors influencing the basic characteristics of each solution are the structural parameter of the PGT τ and the effective diameter of the TC circuit D. By further analysis, it is found that the efficiency varies strictly monotonically with τ and D. Therefore, the two boundary values for the τ and a specific value for the D are adopted to examine the basic characteristics of each solution. Figure 9 shows the efficiency of each solution.…”
Section: Basic Characteristics Analysismentioning
confidence: 99%
“…Jo et al suggested a new input torque coupled HMPST concept, where the hydraulic elements were placed at both the mechanical and hydraulic branches. To evaluate the usefulness of the designed mechanism relative to a prototype TC (TC), the torque ratio and efficiency for all six schemes were analyzed using the performance locus diagram [8]. Linares et al proposed a thorough methodology for designing a continuously variable power split transmission with several types of power flow suitable for an agricultural tractor.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hydrodynamic mechanical power-split (HMPS) transmissions have attracted increasing research interest. [4][5][6] The reasons are twofold. First, the torque converter with low efficiency in an HMPS transmission does not need to be loaded with the full input power of the transmission.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, the effectiveness of the optimization model is not validated. Jo et al 17 presented a new input coupled power-split transmission. They analyzed the TR and efficiency of all feasible solutions by the performance trajectory diagrams.…”
Section: Introductionmentioning
confidence: 99%